Effect of Rosmarinic Acid on the Focal Adhesions of MC3T3-E1 Preosteoblasts on Titanium Surface - Moon-Jin Jeong; Myoung-Hwa Lee; Do-Seon Lim; Soon-Jeong Jeong (The Korean Society of Dental Hygiene Science, 2024)
Background: Focal adhesions (FAs) is the most important process in the first step of osseointegration between preosteoblasts and titanium (Ti). FAs improvement and pre-osteoblasts cell proliferation leads to successful Ti-based dental implants. This study aimed to confirm the applicability of rosmarinic acid (RA) as a functional substance for improving FAs and cell proliferation of MC3T3-E1 preosteoblasts on Ti surfaces during the first stage of osseointegration for successful Ti-based dental implants. Methods: We used MC3T3-E1 preosteoblasts on Ti discs incubated in a medium supplemented with or without 14 μg/ml to decipher the effects of RA on FAs and cell proliferation. FAs and proliferation of MC3T3-E1 cells on Ti discs were assessed via MTT assay. Actin-labeled cells and paxillin contacts were observed and imaged by fluorescent microscopy, and the associated signaling pathways were revealed through western blot analysis. Results: In RA-treated MC3T3-E1 cells on Ti discs, FAs between MC3T3-E1 preosteoblasts and Ti surfaces and the expression of focal adhesion kinase (FAK), phosphorylated FAK and paxillin proteins and filamentous-actin formation increased. RA increased the proliferation of MC3T3-E1 preosteoblasts on the Ti surface as well as the expression of Grab2, Ras, pERK1/2, and ERK1/2. In addition, the expression of secretory leukocyte protease inhibitor and thymosin b4, known as nanomolecules that enhance the interaction between implanted Ti materials and preosteoblasts in the RA-treated MC3T3-E1 preosteoblasts, increased. RA not only increased the FAs of MC3T3-E1 preosteoblasts on the Ti surface through the FAK/Paxillin signaling pathway, but also increased cell proliferation and mitosis through the FAK/Grab2/Ras/ERK1/2 signaling pathway. Conclusion: RA can be applied as an effective functional substrate to improve the FAs and proliferation of MC3T3-E1 preosteoblats on Ti surfaces, which are essential in the first step of osseointegration between implanted Ti and bone tissue for the clinical success of Ti based dental implants.